Distinct functionality of neutrophils in multiple sclerosis and neuromyelitis optica. (February 2016) - Hertwig, Laura; Pache, Florence; Romero-Suarez, Silvina; Stürner, Klarissa H; Borisow, Nadja; Behrens, Janina; Bellmann-Strobl, Judith; Seeger, Bibiane; Asselborn, Natascha; Ruprecht, Klemens; Millward, Jason M; Infante-Duarte, Carmen; et al.
Background: In contrast to multiple sclerosis (MS), lesions in neuromyelitis optica (NMO) frequently contain neutrophils. However, the phenotypic profile of neutrophils in these two distinct pathologies remains unknown. Objective: Our aim is to better understand the potential contribution of neutrophils to NMO and MS pathology. Methods: We performed the first functional analysis of blood neutrophils in NMO and MS, including evaluation of neutrophil immune response (fMLP receptor, TLR2), chemotaxis and migration (CXCR1, CD62L, CD43), regulation of complement (CD46, CD55, CD59), respiratory burst, phagocytosis and degranulation. Results: Compared with healthy controls (HC), neutrophils in NMO and MS show an activated phenotype characterized by an increased surface expression of TLR2 and fMLP receptor. However, contrary to MS neutrophils, NMO neutrophils show reduced adhesion and migratory capacity as well as decreased reduced production of reactive oxygen species (respiratory burst) and degranulation. Conclusion: Although NMO and MS neutrophils display an activated phenotype in comparison with HC, NMO neutrophils show a compromised functionality when compared with MS patients. These results suggest a distinct functional profile of neutrophils in MS and NMO.